Conflicts with jus cogens in international law - Hameed, A (2012)
Jus cogens is a mysterious body of international law. It comprises legal standards which are thought to be superior to those in ordinary international law, namely, international treaties, customary international law, and general principles of law. The title of this study – ‘Conflicts with Jus Cogens in International Law’ – condenses its main aims. The study examines conflict-situations between jus cogens rules and rules of ordinary international law. The study is divided into four Parts. Part I clarifies what jus cogens status means and how jus cogens rules are made. Part II analyses some of the different ways in which legal rules come into conflict with each other. I seek to push the boundaries of our understanding of legal conflict, and I also construct a typology of legal conflict. In Part III, I apply the analysis of conflict in Part II to the jus cogens context by identifying and classifying situations where rules of ordinary international conflict with jus cogens rules. Finally, Part IV explores the consequences of the conflicts with jus cogens which were identified in Part III. What we see is that the consequences of these conflicts are varied. Most strikingly, however, we find that in some cases jus cogens rules are being defeated by rules of ordinary international law. This challenges the orthodox thinking that jus cogens rules are straightforwardly superior to ordinary international law, in the sense that they always prevail in conflict-situations. But while the conclusion of the study may seem radical, it is informed by theoretical writing about law and about how rules conflict. Ultimately, the study seeks to improve our understanding of jus cogens rules in international law, as well as the more general problem of how legal rules conflict with each other.